Wound Healing Effect Of Various Extracts Of Adhatoda Vasica - G.VINOTHAPOOSHAN; K.SUNDAR (International Journal of Pharma and Bio Sciences, 2010)
In the Present study, methanolic, chloroform and diethyl ether extracts of Adhatoda vasica Plants were evaluated for its wound healing activity in the form of Ointment dosage form in excision wound model in albino rats. The methanolic extract ointment of Adhatoda vasica showed a significant effect in excision wound model as comparable to standard drug and other two extracts of ointment, by calculating the parameters, percentage closure of excision wound model. The Isolated compounds were characterized by instrumental analysis and IR.